Pengembangan Potensi Desa Pattojo Kecamatan Liliriaja Kabupaten Soppeng melalui Edukasi Anak - Yusuf, Raidah Intizar; Ramadhani, Sri; Ali, Moch Rival Rafi; Satril, Satril (Journal Social Engagement: Jurnal Pengabdian Kepada Masyarakat, 2025)
Abstract Pattojo Village is located in Liliriaja District, Soppeng Regency, South Sulawesi. The village area is approximately 10 km² and is surrounded by fertile agricultural land and abundant natural resources, including rivers and clean water springs. Pattojo Village is inhabited by approximately 2,623 people, consisting of 1,288 men and 1,335 women. There are approximately 832 heads of families living in two main hamlets: Dabbare Hamlet and Pattojo Hamlet. The composition of the population is diverse, with most of them being farmers and workers in the agricultural sector. The economy of Pattojo Village is largely dependent on the agricultural sector. Many local residents are engaged in rice farming as the main commodity, in addition to other horticultural crops. In addition, livestock is also a source of income for several families, with livestock such as cows, goats, and chickens. Local trade is also growing, with traditional markets being a meeting place for traders and buyers. Based on the results of observations, it was found that one of the needs that can be met by KKN students is the need for education. Several programs were launched such as IT socialization, literacy and numeracy, and reading and writing the Quran. The implementation of the Regular KKN work program in the Village was successful despite facing challenges. This success was achieved due to the collaboration between KKN students, village government, officials, and the community. Various activities have been carried out, such as IT seminars that provide junior high school students with practical technology skills, and literacy and numeracy programs that improve the basic abilities of elementary school students. The learning activities of reciting the Quran at TPQ Al-Madinah went smoothly with better results for students in reading the Quran using tajwid. Abstrak Desa Pattojo terletak di Kecamatan Liliriaja, Kabupaten Soppeng, Sulawesi Selatan. Wilayah desa ini memiliki luas sekitar 10 km² dan dikelilingi oleh lahan pertanian yang subur serta sumber daya alam yang melimpah, termasuk sungai dan mata air bersih. Desa Pattojo dihuni oleh sekitar 2.623 jiwa, yang terdiri dari 1.288 laki-laki dan 1.335 perempuan. Terdapat sekitar 832 kepala keluarga yang tinggal di dua dusun utama: Dusun Dabbare dan Dusun Pattojo. Komposisi penduduknya beragam, dengan sebagian besar merupakan petani dan pekerja di sektor pertanian. Ekonomi Desa Pattojo sebagian besar bergantung pada sektor pertanian. Penduduk setempat banyak yang menggeluti pertanian padi sebagai komoditas utama, di samping tanaman hortikultura lainnya. Selain itu, peternakan juga menjadi sumber pendapatan bagi beberapa keluarga, dengan ternak seperti sapi, kambing, dan ayam. Perdagangan lokal juga berkembang, dengan pasar tradisional yang menjadi tempat bertemunya para pedagang dan pembeli. Berdasarkan hasil observasi ditemukan bahwa salah satu kebutuhan yang dapat dipenuhi oleh mahasiswa KKN ialah kebutuhan edukasi. Sejumlah program dicanangkan seperti sosialisasi IT, literasi dan numerasi serta baca tulis Quran. Pelaksanaan program kerja KKN Reguler di Desa berlangsung sukses meskipun menghadapi tantangan. Keberhasilan ini tercapai oleh karena adanya kolaborasi antara mahasiswa KKN, pemerintah desa, aparat, dan masyarakat. Beragam kegiatan telah dijalankan, seperti seminar IT yang memberikan siswa SMP keterampilan teknologi praktis, dan program literasi serta numerasi yang meningkatkan kemampuan dasar siswa SD. Kegiatan pembelajaran mengaji di TPQ Al-Madinah berjalan lancar dengan hasil santri yang lebih baik dalam membaca Al-Qur'an menggunakan tajwid.